STUDENTS’ LEARNING STRATEGIES IN WRITING ESSAY (A CASE STUDY OF ENGLISH EDUCATION STUDENTS AT UIN JAMBI - Fajriah, Anatul (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2021)
The students used different strategies in their learning process in order to make their learning process enjoyable and effective. Here the researcher conducted research with a purpose to identify the learning strategies in writing essay used by the students of English Education Program. This is a qualitative research and used case study as research method. The subject of the research was 22 students who have good score in writing essay. The data of this research are the result of interview with students and documentation. The research finding showed that the students used six learning strategies in writing essay, memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies. The students used all of strategy in their writing essay process but different way.